An Investigation into the Efficacy of a Structured Teaching Program on Hypnobirthing Knowledge Among Final-Year GNM Students in Designated Nursing Schools in Vijayapur - Anurupa Chalwadi (International Journal of Women's Health Nursing And Practices, 2024)
Pregnancy is a lengthy journey that is best navigated with support. The process of labor is often overwhelming, involving intense sensations and emotions. Women benefit from having supportive individuals with them to assist in coping with the challenges of labor. Regardless of the level of childbirth preparation or prior experiences, women require a combination of psychological and physical coping methods during labor and childbirth. The term “labor” refers to the rhythmic contraction and relaxation of uterine muscles, leading to the gradual effacement and dilation of the cervix, ultimately resulting in the expulsion of the products of conception—comprising the fetus, placenta, and membranes—through the birth canal.
Keywords: Pregnancy; birth canal; fetus; placenta; psychological and physical coping methods